Determinants of Financial Performance in The Indonesian Islamic Insurance Industry - Iman Pirman Hidayat; Irman Firmansyah (ETIKONOMI, 2017)
The purpose of this study is to determine the role of the board of directors as an operating executive, as the company's supervisory board of commissioners, the proportion of managerial ownership and institutional ownership as well as leverage on the financial performance of Islamic insurance industry. The method used is multiple regression analysis and Moderated Regression Analysis. Data of company successfully researched as many as 15 Islamic insurance companies in Indonesia with a study period of 2011 to 2015. The results showed that the board does not affect the financial performance of Takaful. Commissioners, managerial ownership, institutional ownership and leverage positive effect on the financial performance of Islamic insurance industry in Indonesia. The size of the company weakens the relationship between the number of directors and leverage to financial performance, and did not moderate the relationship between the number of commissioners, managerial ownership and institutional ownership of the financial performance of Islamic insurance industry..DOI: 10.15408/etk.v16i1.4648